Implication of Student Centered Learning (SCL) Approach Against Students Learning Achievement of Theme Regional Natural Resources Analysis in Geography of Natural Resources Course (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2020)
The aims of this research were (1) to describe the implementation of the Students Centered Learning (SCL) approach and the study method of material on the theme of regional natural resources analysis in the Geography of Natural Resources course, and (2) to find the implications of the SCL approach to learning achievement. The research method was a quasi-experimental with posttest only controls group design. The class as the samples determine by purposive sampling which distinguished of the experimental class and the control. The collected data were analyzed by t-test, after the data were normally distributed and homogeneous variety. The results of this study describe that the implementation of the SCL approach is obtain in 4 (four) syntax: brainstorming, grouping & exploring, do projects, and seminars, with the study method is structured tabulation analysis by explaining classification, and